A novel family of diarylpyrimidines (DAPYs) featuring a diatomic linker: Design, synthesis and anti-HIV activities. Issue 20 (15th October 2015) - Gu, Shuang-Xi; Qiao, Heng; Zhu, Yuan-Yuan; Shu, Qi-Chao; Liu, Hui; Ju, Xiu-Lian; De Clercq, Erik; Balzarini, Jan; Pannecouque, Christophe
Graphical abstract: Abstract: To improve the conformational flexibility and positional adaptability of the traditional diarylpyrimidines (DAPYs), a family of diarylpyrimidines featuring a C–N diatomic linker between the left wing benzene ring and the central pyrimidine was firstly designed, synthesized, and evaluated for in vitro anti-HIV activity. Most of target molecules showed excellent activities against wild-type (WT) HIV-1. Among them the most potent two compounds12h and12r displayed extremely potent WT HIV-1 inhibitory activities with an EC50 of 2.6 nM and 3.0 nM, respectively, while their selective index (CC50 /EC50 ) values were both over 1000. Another compound12b (EC50 14.9 nM) was also noteworthy due to its high SI of 18, 614. Moreover, all of compounds were evaluated for their WT HIV-1 reverse transcriptase activities, which shown that the newly synthesized CH 2 NH -DAPYs bind to HIV-1 RT and belong to the genuine NNRTIs. However, the synthesized compounds lack the activities against HIV-1 double mutant (RES056) and HIV-2 (ROD). Thus it is an upcoming objective to improve the activities against HIV-1 double mutants.